2021
DOI: 10.1021/acsomega.1c05586
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose and Graphene Oxide Aerogels for Adsorption and Removal Methylene Blue from an Aqueous Environment

Abstract: The characteristics of aerogel materials such as the low density and large surface area enable them to adsorb large amounts of substances, so they show great potential for application in industrial wastewater treatment. Herein, using a combination of completely environmentally friendly materials such as cellulose nanofibers (CNFs) extracted from the petioles of the nipa palm tree and graphene oxide (GO) fabricated by simple solvent evaporation, a composite aerogel was prepared by a freeze-drying method. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…MB is widely used in the textile industry with a heterocyclic aromatic structure and can cause many adverse impacts after its intake, such as nausea, vomiting, and mental confusion. 49 The PCNF composite aerogel with negatively charged surfaces may have a strong adsorption capacity toward the positively charged MB dyes. Moreover, the PDA layer may also play a role as an electron acceptor through π−π stacking interactions with the conjugated structures of MB (unsaturated double bonds).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MB is widely used in the textile industry with a heterocyclic aromatic structure and can cause many adverse impacts after its intake, such as nausea, vomiting, and mental confusion. 49 The PCNF composite aerogel with negatively charged surfaces may have a strong adsorption capacity toward the positively charged MB dyes. Moreover, the PDA layer may also play a role as an electron acceptor through π−π stacking interactions with the conjugated structures of MB (unsaturated double bonds).…”
Section: Resultsmentioning
confidence: 99%
“…MB is widely used in the textile industry with a heterocyclic aromatic structure and can cause many adverse impacts after its intake, such as nausea, vomiting, and mental confusion . The PCNF composite aerogel with negatively charged surfaces may have a strong adsorption capacity toward the positively charged MB dyes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was found that this hybrid ensures an effective easy separation process and reusability, rendering it a potential, economical and effective adsorbent in antibiotic removal from wastewater. Recently, Nguyen and coworkers prepared aerogels based on CNFs/GO using a freeze-drying method for removal and adsorption of methylene blue from aqueous environments, 119 as schematized in Fig. 11(C).…”
Section: Cnfs/graphene Oxide Nanosystemsmentioning
confidence: 99%
“…Dyes in water can adversely affect ecosystems and human health. Adsorption has become one of the most effective wastewater treatment methods because of its low cost, simple operation, and high efficiency [ 1 , 2 , 3 ]. Graphene aerogels are porous (porosity can reach more than 99%), which can provide sufficient transport channels for the diffusion of pollutants when they are adsorbed to improve the adsorption efficiency of adsorbents [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%